Đánh giá diễn biến và phân tích nguồn gốc bản chất hóa học nước mưa từ Ninh Bình trở ra. - Khánh, Nguyễn Hồng (VNU Journal of Science: Natural Sciences and Technology; Vol 20 No 2, 2004)
The aim of this paper is to summarize the results of a study on the variation and trend of rainwater chemistry for the Northern Vietnam in framework of the State Research Project "Research, assessment and suggestion of the control measures on acid rain in Northern Part of Vietnam", 2000-2002. The network station (7 stations) has been covered the whole territory representing for the mountain, rural, urban and coastal regions of North Vietnam. Rainwater chemistry was carried out in the mentioned regions by using semi-automatic collectors. Data resulted show that acid rain has occurred on the total study network. The variations (both spatial and temporal) of rainwater chemistry are closely related with topography, air emission and air circulation. Acid rain is even found at the Bac Quang being the "bag" rainfall region of North Vietnam.